A supervisory style that combines the concepts of Amicable and Dialogue for students practicing teaching professional experience in Thai language - Chimmode, Songrid; Chanthamat, Thanong; Sawangjai, Phuangpen; Suanmalee, Ubolwan (Journal of Humanities and Social Sciences Review, 2025)
The objective of this study was to study and present the results of using a supervision model integrating the concepts of Kalyanamitta and Dialogue, and the Thai language learning management guidelines for Thai language student teachers in the academic year 2023. This study was based on qualitative research guidelines in terms of participatory action research between the researchers as supervisors, school administrators, mentor teachers, student teachers, and students. The target group was 14 Thai language student teachers who were 4th-year students of the Thai Language Department, Faculty of Humanities and Social Sciences, Phetchaburi Rajabhat University. Instruments used in this study were individual and focus group interviews, including document analysis and participatory observation. The research results revealed that the supervision model integrating the concepts of Kalyanamitta and Dialogue for Thai language student teachers in academic year 2023 had 2 periods, totaling 6 steps. For guidelines on organizing Thai language learning for student teachers, there were two approaches. The first approach was organizing learning in the Thai language subject, and the second was organizing learning to develop analytical reading and interpreting skills. This form of supervision promoted students’ confidence in teaching the Thai language subject effectively.